2024
DOI: 10.1142/s0192415x24500289
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Licorice: The Preparation, Chemical Composition, Bioactivities and Its Applications

Xiaoyu Ji,
Ning Liu,
Shucheng Huang
et al.

Abstract: Licorice (Glycyrrhiza) is a medicinal and food homologue of perennial plants derived from the dried roots and rhizomes of the genus Glycyrrhiza in the legume family. In recent years, the comprehensive utilization of licorice resources has attracted people’s attention. It is widely utilized to treat diseases, health food products, food production, and other industrial applications. Furthermore, numerous bioactive components of licorice are found using advanced extraction processes, which mainly include polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 184 publications
0
2
0
Order By: Relevance
“…Licorice is a medicinal herb with a 2000-year history of application in traditional Chinese medicine. The most studied and documented benefits of glabridin from licorice are its anti-inflammatory properties, and its antibacterial activities have also been described, albeit less frequently, in the reported literature ( Simmler et al, 2013 ; Ji et al, 2024 ). L. monocytogenes is a dangerous foodborne pathogen that poses a serious threat to public health and causes substantial economic losses for society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Licorice is a medicinal herb with a 2000-year history of application in traditional Chinese medicine. The most studied and documented benefits of glabridin from licorice are its anti-inflammatory properties, and its antibacterial activities have also been described, albeit less frequently, in the reported literature ( Simmler et al, 2013 ; Ji et al, 2024 ). L. monocytogenes is a dangerous foodborne pathogen that poses a serious threat to public health and causes substantial economic losses for society.…”
Section: Discussionmentioning
confidence: 99%
“…, Glycyrrhiza inflata Bat. , and Glycyrrhiza glabra L. Studies have shown that licorice is used in flavoring and sweetening agents, demulcents, expectorants, and anti-allergic and anti-inflammatory agents ( Ji et al, 2024 ). It has widespread pharmacological effects on human diseases, including atherosclerosis, immunodeficiency, hormone deficiency, endocrine disruption, cancer, and skin diseases ( Kwon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%